Effectiveness of Simple Individual Psychoeducation for Bipolar II Disorder - Yuka Saito-Tanji; Emi Tsujimoto; Reiko Taketani; Ami Yamamoto; Hisae Ono (Case Reports in Psychiatry)
Several studies have proven the effectiveness of psychoeducation in bipolar II disorder patients; however, simpler psychoeducation is needed in daily medical practice. Therefore, we devised a simple individual psychoeducation program, which involved 20-minute sessions spent reading a textbook aloud in the waiting time before examination. Here, we report a successful case of simple individual psychoeducation with a patient with bipolar II disorder, a 64-year-old woman who had misconceptions surrounding her mood due to 24 years of treatment for depression. Her perception of mood state, particularly mixed state, was dramatically changed, and her quality of life was improved after the simple individual psychoeducation. This case suggests that the simple individual psychoeducation could be effective for bipolar II disorder by improving understanding of the disease and by meeting different individual needs.